2017
DOI: 10.1080/16546628.2017.1412794
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulated HOTAIR induced by fatty acids inhibits PTEN expression and increases triglycerides accumulation in HepG2 cells

Abstract: Non-alcoholic fatty liver disease (NAFLD) is characterized by hepatic lipid accumulation unrelated to excess alcohol intake, in which the hepatic expression of phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is inhibited. Long non-coding RNA HOTAIR suppresses PTEN expression in hepatic stellate cells during liver fibrosis, and it is involved in liver lipid dysregulation. In this study, we evaluated whether the PTEN down-regulation and lipid accumulation in hepatic cells might be mediated by HOTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…steatosis), while the ‘second hit’ is the progression of steatosis to nonalcoholic steatohepatitis (NASH) ( 8 ). This progression is often associated with the release of cytokines, and a previous study identified a central role for the overexpression of pro-inflammatory cytokine tumour necrosis factor (TNF)-α mRNA in the aetiology of NASH ( 9 ). Human liver steatosis is associated with the accumulation of excess oleic acid (OA), a monosaturated omega-9 fatty acid and end product of de novo fatty acid synthesis ( 10 ).…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…steatosis), while the ‘second hit’ is the progression of steatosis to nonalcoholic steatohepatitis (NASH) ( 8 ). This progression is often associated with the release of cytokines, and a previous study identified a central role for the overexpression of pro-inflammatory cytokine tumour necrosis factor (TNF)-α mRNA in the aetiology of NASH ( 9 ). Human liver steatosis is associated with the accumulation of excess oleic acid (OA), a monosaturated omega-9 fatty acid and end product of de novo fatty acid synthesis ( 10 ).…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…HOTAIR is increased in different forms of cancers and involved in diverse cellular functions. In NAFLD, free fatty acid treatment promotes TG accumulation in HepG2 cells, significantly induces HOTAIR expression and inhibits phosphatase and tensin homolog expression[ 139 ]. A recent study reported that HOTAIR was activated in NAFLD, and HOTAIR knockdown significantly inhibited the development of NAFLD via mediation of miR-130b-3p/ROCK1/AMPK axis, further suggesting a target for NAFLD[ 140 ].…”
Section: Emerging Role Of Ncrnas In the Pathogenesis Of Nafldmentioning
confidence: 99%
“…NEAT1 expression aggravated free fatty acid (FFA)-induced lipid accumulation in hepatocytes by regulating the c-Jun/SREBP1c axis by sponging miR-139-5p. Indeed, NEAT1 heightening is followed by acetyl-CoA carboxylase (ACC) and fatty acid synthase (FAS) mRNA enhancement in both in vivo and in vitro models of NAFLD [111] . A preclinical study showed that the knockdown of NEAT1 in hepatocytes hampered lipid content and liver disease through the modulation of ACC and FAS expression.…”
Section: Nuclear Enriched Abundant Transcript 1 (Neat1)mentioning
confidence: 99%